Editorial - Thematic Issue: Black, African and Afrodiasporic Theatricalities (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Information about the content of the: Thematic Issue: Black, African and afrodiasporic theatricalities.
Keywords: editorial; articles; urdimento